Life Cycle Assessment of welding technologies for thick metal plate welds. (1st December 2015) - Sproesser, Gunther; Chang, Ya-Ju; Pittner, Andreas; Finkbeiner, Matthias; Rethmeier, Michael
Abstract: Life Cycle Assessment (LCA) is applied in evaluating environmental impacts of state-of-the-art welding technologies. Manual Metal Arc Welding (MMAW), Laser Arc-Hybrid Welding (LAHW) and two Gas Metal Arc Welding (GMAW) variants are used to join a plate of 20 mm thick structural steel. The LCA results indicate that for 1 m weld seam, MMAW causes the highest environmental impacts in global warming potential (GWP), eutrophication potential (EP), acidification potential (AP), and photochemical ozone creation potential (POCP) among the selected processes, and the LAHW variant performances the least. Filler material and electricity consumptions generally dominate the impacts and reach shares of up to 80% and 61% in the respective impact categories. However, electrode coating consumption in MMAW remarkably contributes impacts on AP and EP, for instance 52% of AP and 76% of EP. Strategies for improvement of the applied welding technologies are discussed. Highlights: Four welding processes are evaluated by Life Cycle Assessment. Laser Arc-Hybrid welding is superior among the investigated processes. Filler metal, electricity and electrode coating dominate environmental impacts.